(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2019)
In the present study, quantum computational methods such as semi empirical, Hartree fock and density functional theory (DFT) are used for the analysis of molecular structure of 4, 8-di methyl, 2, 6 - di phenyl, 1, 5 - di hydro S Indacene. Vibrational analysis was carried out using DFT method with the basis set B3LYP/6– 31G (d, p) and the infrared and Raman spectra of title compound were reported. Frequency assignments of the vibration spectra were carried out with potential energy distribution (PED). Optimization of the title compound were calculated by the methods AM1, PM6, HF/6-31G and B3LYP/6-31G (d, p) basis set in gas phase. Furthermore, effect of substituents of the title molecule on its electronic properties such as HOMO-LUMO energy gap, absorption maxima and oscillator strengths in UV-Vis spectrum, NBO analysis, TDOS, Fukui function and the local softness and eletrophilicity indices were calculated. The thermodynamic properties have also been calculated and predicted the relationship of these properties with temperature.